Civil Liability in Protection and Management of the Environment Post Law No. 11 Year 2020 Concerning Creation of Work - Ilham Langgai (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This paper will discuss the protection and management of the environment after Law no 11 of 2020 concerning Job Creation which has a negative impact on the sustainability of the Environment in Indonesia in terms of Civil Liability, which is due to the influence of an addition, change and deletion in Law no. 11 of 2020 concerning Job Creation in Law no. No. 32 of 2009 concerning Environmental Protection and Management, Law no. 17 of 2019 concerning Water Resources, Law no. 39 of 2014 concerning Plantations, and Law no. 41 of 1999 concerning Forestry, and its derivative regulations.